2015
DOI: 10.1002/cbic.201500100
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Structural Determinants for the Substrate Specificity in the Zinc‐Dependent Alcohol Dehydrogenase CPCR2 from Candida parapsilosis

Abstract: Zinc-dependent alcohol dehydrogenases (ADHs) are a class of enzymes applied in different biocatalytic processes ranging from lab to industrial scale. However, one drawback is the limited substrate range, necessitating a whole array of different ADHs for the relevant substrate classes. In this study, we investigated structural determinants of the substrate spectrum in the zinc-dependent ADH carbonyl reductase 2 from Candida parapsilosis (CPCR2), combining methods of mutational analysis with in silico substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Candida parapsilosis alcohol dehydrogenase 5 (cpADH5), formerly also named as Candida parapsilosis carbonyl reductase 2 (CPCR2), belongs to the zinc‐dependent medium chain alcohol dehydrogenases (MDRs) family . cpADH5 has a broad substrate range toward aliphatic ketones, keto esters, cyclic ketones, and aryl or aromatic substituted secondary alcohols . Yamamoto and co‐workers reported that cpADH5 is capable of oxidizing secondary alcohols such as ( S )‐2‐butanol, ( S )‐1‐phenylethanol, and achiral 2‐propanol .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Candida parapsilosis alcohol dehydrogenase 5 (cpADH5), formerly also named as Candida parapsilosis carbonyl reductase 2 (CPCR2), belongs to the zinc‐dependent medium chain alcohol dehydrogenases (MDRs) family . cpADH5 has a broad substrate range toward aliphatic ketones, keto esters, cyclic ketones, and aryl or aromatic substituted secondary alcohols . Yamamoto and co‐workers reported that cpADH5 is capable of oxidizing secondary alcohols such as ( S )‐2‐butanol, ( S )‐1‐phenylethanol, and achiral 2‐propanol .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cpADH5 has been investigated in detail by employing computational approaches. Carbonyl reduction mechanism as well as structural determinants of substrate spectrum was determined by using quantum mechanichs/molecular mechanics (QM/MM) techniques . Natural substrates and thus, function of the cpADH5 were predicted through virtual screening and QM/MM calculations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the comparative study, CAST/ISM was tested in what we consider to be a questionable procedure, specifically when pitching it against the subsequent OmniChange experiments: Four single one‐residue sites were first chosen, three from a previous study (C57, W116 and L119), and one from a computational analysis (W286). Then conventional NNK‐based SM by using QuikChange was applied individually to all four single‐residue sites, as schematically illustrated in Figure B with B, C, E, and H representing the single residues.…”
Section: Figurementioning
confidence: 89%
“…In this study we report a first comprehensive comparison of iterative and simultaneous site saturation mutagenesis for the example of improved cpADH5 activity. Three amino acid positions (Figure ; C57, W116 and L119) were selected from previous literature and one additional residue was selected from computational analysis (Figure ; W286). In total, four residues were subjected to simultaneous multiple site saturation or iterative recombination (exploring 17 paths) in order to improve the oxidation activity of cpADH5 toward methyl 3‐hydroxyhexanoate.…”
Section: Introductionmentioning
confidence: 99%